Risk factors for postoperative pulmonary complications in elderly patients receiving elective colorectal surgery: A retrospective study - Dai, Yuanqiang; Sun, Guolin; Hu, Hongli; Wang, Chun; Wang, Hengyue; Zha, Yanping; Sheng, Ying; Hou, Jiong; Bian, Jinjun; Bo, Lulong (Frontiers in Oncology, 2022)
Study objective Postoperative pulmonary complications (PPCs) are common and associated with adverse outcomes impairing long-term survival and quality of recovery. This single-centered retrospective study aimed to examine factors associated with PPCs in patients receiving elective colorectal surgery aged ≥60 years. Methods Between January 2019 and December 2019, 638 patients at the Shanghai Changhai Hospital who had received elective surgery for colorectal cancer were enrolled in this study. Patients were divided into the PPC group (n=38) and non-PPC group (n=600). Neutrophil–lymphocyte ratio (NLR), platelet–lymphocyte ratio (PLR), red blood cell distribution width (RDW), and systemic inflammatory index (SII) were selected and caculated to indicate preoperative and postoperative inflammatory status. Receiver operating characteristic curve and bivariate correlation analyses were performed to evaluate the identified risk factors. Main results The overall incidence of PPCs was approximately 5.96%. Multivariate regression analysis identified age (OR = 1.094, 95%CI 1.038–1.153, P = 0.001), preoperative RDW (OR = 1.159, 95%CI 1.025–1.309, P = 0.018), and preoperative SII (OR = 1.001, 95%CI 1.000–1.003, P = 0.035) as independent risk factors for PPCs. The cut-off values of age, preoperative RDW, and preoperative SII for predicting PPCs were 69.5 (sensitivity 0.658, specificity 0.653), 13.2 (sensitivity 0.789, specificity 0.552) and 556.1 (sensitivity 0.579, specificity 0.672), respectively. Conclusions Age, preoperative RDW, and preoperative SII were identified as independent risk factors for PPC occurrence in elderly patients receiving elective colorectal surgery. Further studies are warranted to evaluate whether normalization of preoperative RDW and SII, as modifiable risk factors, are associated with improved surgical outcomes.